Teaching second grade [a practical resource packed with winning strategies & activities that reach & teach all learners in this very important grade] - SchifferDanoff, Valerie (New York Scholastic Professional Books, 2000)
"Cross-curricular activities, organizational strategies, management tips, patterns & graphic organizers, literature links, reading & writing mini-lessons, pocket chart ideas."
"Grade 2"-- Cover.
Includes reproducible templates.
Keywords: Creative activities and seat work